Alcohol policy as defined by path dependency and Prohibition - Setty, Kathryn, author; Hitt, Matthew, advisor; Saunders, Kyle, advisor; Korostyshevsky, David, committee member (Colorado State University. Libraries, 2022)
Across the United States there is noticeable variance regarding alcohol regulations from state to state. More restrictive states allow for dry counties, Sunday sale bans, and tightly regulate the types of alcohol that can be sold outside of liquor stores. Conversely, less restrictive states allow for 24/7 purchase, drive through liquor stores, open container zones, and decreased regulation on type of alcohol sold at convenience stores. This variance is not explained by modern or historic partisanship, nor general religiosity of a given area. Religiosity classified by high amounts of Protestantism along with historic rates of Protestantism have the highest amount of explanatory value for states with more restrictive alcohol laws. Utilizing the theoretical foundations of path dependency and increasing returns this paper posits that current variance in alcohol policies across states can be accounted for by the historic levels of support for the 18th Amendment and the temperance movement as represented by historic Protestantism in a given state. That is, after reaching a critical juncture in the passage of the 18th Amendment, states which had been more inclined to prohibit alcohol sales reached policy equilibrium that enabled regulation to persist. This paper will use an original data set that combines historical data from the U.S Census and archival data with modern measures of religiosity, along with constructed composite variables that rank each state's alcohol policy over time as most restrictive to least restrictive. This data, presented in a time series cross section analysis, will illustrate the historic relationship between Prohibition support and modern alcohol policy. History has a prevailing, lasting impact on the modern era which can be illustrated through policy and the power paradigms that persist within our society.